Diagnosis of placental malaria in poorly fixed and processed placental tissue. (December 2016) - Liu, Yunhao; Griffin, Jennifer; Muehlenbachs, Atis; Rogerson, Stephen; Bailis, Anya; Sharma, Rajni; Sullivan, David; Tshefu, Antoinette; Landis, Sarah; Kabongo, Jean-Marie; Taylor, Steve; Meshnick, Steven
Abstract Background Placental histopathology has been considered the gold standard for diagnosis of malaria during pregnancy. However, in under-resourced areas placental tissue is often improperly fixed and processed; the resulting formalin pigment is difficult to distinguish from malaria pigment. This study examines two alternative diagnostic methods: polymerase chain reaction (PCR) and a novel immunohistochemistry (IHC)-based method using an antibody against histidine-rich protein 2 (HRP2). Methods Placental histopathology from 151 pregnant women in Kinshasa was assessed by two blinded microscopists and compared with peripheral blood PCR and IHC for HRP2. The Cohen's kappa coefficients were calculated to assess the test agreement. The sensitivity and specificity of individual tests were calculated using PCR or IHC as the reference standard as well as latent class analysis (LCA). Results PCR and IHC correlated fairly well. The correlation between the two blinded microscopists was poor, as there was widespread formalin pigment. Using LCA, all of the tests had high specificities. The most sensitive test was IHC (67.7 %), with PCR as second-best (56.1 %). Conclusions PCR and/or IHC are suitable diagnostics when the presence of formalin pigment substantially compromises placental histopathology.